Strategia i procesy zarządzania łańcuchem dostaw : teoria i praktyka - Rodawski, Bartłomiej (Supply Chain Management Strategy and Processes : Theory and Practice, 2009)
The paper consists of two parts. Firstly, the theoretical part presents the idea of supply chain management, its strategy as well as process typology. The latter is based on the SCOR model. Second part provides two short case studies: process of forming supply chain for a new product (automotive company) and process of finished goods delivery (ceramic tiles producer). Cursory analysis of both cases proves that there is no coherence between SCM strategy and processes. Supply chains (processes) described in the paper suffer from lack of integration and synchronization. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 337-346